DAMPAK PENERAPAN E-DOCUMENT PADA PEMBIAYAAN PERDAGANGAN INTERNASIONAL (TRADE FINANCE) MENGGUNAKAN LETTER OF CREDIT (L/C) - Ayu Afrizza Anggraeni (2023)
International Trade Finance is an essential service in international trade transactions. This research aims to evaluate the implementation of paper and e-documents in international trade finance using Letter of Credit (L/C) as the method. The research methodology employed a descriptive approach. Analysis was conducted on various aspects of trade finance, including the use of paper and e-documents, payment processes, efficiency, and security. The findings of this research are expected to provide a better understanding of the utilization of paper and e-documents in international trade finance using Letter of Credit (L/C).